Media coverage of health crisis in Malaysia: A framing analysis of covid-19 pandemic - Chan, Hoi Lun (2023)
The Covid-19 pandemic has been a global threat to human life since its outbreak in December 2019, originating from China. Malaysia reported its first case in January 2020. Given the global reach of the pandemic, increased media coverage was expected. Therefore, it is crucial to examine how mainstream and alternative media in Malaysia frame Covid-19 in terms of the type of frames used, sources of information, and slant of news. The study aims to achieve three objectives: (1) to investigate the type of frames used by selected newspapers in their coverage of the Covid-19 pandemic, (2) to determine the sources of information used by the selected newspapers during the pandemic, and (3) to examine the slant of news reported by the selected newspapers during the pandemic. The methodology involves using summative content analysis, including quantitative content analysis to investigate the framing of Covid-19 coverage on online news portals and qualitative content analysis to identify themes or patterns. The results showed that both mainstream and alternative news portals predominantly used the human-interest frame to report on Covid-19. In terms of sources of information, NST and Malaysiakini used all sources of information for their Covid-19 related articles, with no significant gap between the usage of these sources by either news portals. In terms of the slant of news, NST and Malaysiakini predominantly employed a neutral tone, followed by an alarming tone, with alarming news articles focusing on the high number of infections, death tolls, and potential for catastrophic outbreaks